Cellular response within the periodontal ligament on application of orthodontic forces - Nazeer Ahmed Meeran (Wolters Kluwer Medknow Publications, 2013)
During application of controlled orthodontic force on teeth, remodeling of the periodontal ligament (PDL) and the alveolar bone takes place. Orthodontic forces induce a multifaceted bone remodeling response. Osteoclasts responsible for bone resorption are mainly derived from the macrophages and osteoblasts are produced by proliferations of the cells of the periodontal ligament. Orthodontic force produces local alterations in vascularity, as well as cellular and extracellular matrix reorganization, leading to the synthesis and release of various neurotransmitters, cytokines, growth factors, colony-stimulating factors, and metabolites of arachidonic acid. Although many studies have been reported in the orthodontic and related scientific literature, research is constantly being done in this field resulting in numerous current updates in the biology of tooth movement, in response to orthodontic force. Therefore, the aim of this review is to describe the mechanical and biological processes taking place at the cellular level during orthodontic tooth movement.